1648 Raised levels of interleukin 1β, interleukin 1 receptor antagonist and G-CSF predict fatality among encephalitis patients infected with enterovirus 71. Issue 3 (9th February 2012) - Griffiths, M; Ooi, M H; Wong, S C; Mohan, A; Podin, Y; Perera, D; Chieng, C H; Tio, P H; Cardosa, M J; Solomon, T
Abstract : Background: Enterovirus 71 (EV71) is the commonest global cause of sporadic encephalitis. The encephalitis is associated with fatal cardiopulmonary collapse. There is no effective treatment. Pathophysiology is poorly understood. Aim: To explore the relationship between cytokine responses in cerebral and vascular compartments and patient outcome. Methods: Thirty cytokines were measured in cerebrospinal fluid (CSF) and sera from 85 Malaysians with EV71 infection, exhibiting either uncomplicated illness (n=45), meningitis (n=8), encephalitis (n=27) or encephalitis with cardiopulmonary collapse (n=6). Four of the latter patients died. Results: Patients who later required cardiac support had significantly raised concentrations of G-CSF, Interleukin-1β (IL-1β) and IL-1 receptor antagonist in the CSF and sera at admission (p=0.0005; p=0.004; p=0.029 respectively for sera). Sera cytokine levels were significantly associated with death (p=0.04). Combining the sera G-CSF:IL-5 ratio with clinical features at admission accurately predicted fatality (Sensitivity 100%, Specificity 96%). Conclusion: Cytokine responses in the vascular compartment predicted fatal outcome during EV71 infection. Il-1β has a negative inotropic action on the heart. Il-1 receptor antagonist (antagonist to IL-1β) and G-CSF are currently being assessed as treatments for acute cardiac impairment. The findings suggest we have identified functional markers of EV71 related cardiac dysfunction and potential treatments.